Death in Haruki Murakami’s Novels: Shadow, Soul, and Sex - Hang, Le Thi Diem (Animo Repository, 2021)
From medieval to modern and postmodern times, thoughts about death have been among the most important subjects in literature. Among writers who have discussed death, Haruki Murakami addressed not only the notions of death and life after death but also the nature of death through existence. His point of view becomes metaphysical reflections. Through cultural semiotics, psychoanalysis, and existential theory, I show that death is associated with mythical thought and the hybrid between Japanese cultural tradition and Western existentialism. In Murakami’s novels, death represents Mono no aware and the beauty of melancholy presage. Life after death is associated with shadow, soul, and a new existence in which death and sex have expressed the desire for eternal freedom. Death is a mixing body and soul, nature and culture. Through death, Murakami created new aesthetic categories.